ANALISIS TINGKAT KESEHATAN BANK SEBELUM DAN SETELAH DIAKUISISI MENGGUNAKAN METODE RGEC (STUDI KASUS PT BANK KB BUKOPIN TBK) - Pratama, Jodi Aditya; Mirati, R. Elly; Purwaningrum, Endang (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This research is motivated by the significant performance decline of PT Bank KB Bukopin Tbk. after being acquired by KB Kookmin Bank, marked by a drastic increase in Non Performing Loan and net profit losses. The purpose of this study is to analyze the health level of PT Bank KB Bukopin Tbk. before and after the acquisition. This study uses the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) method, represented by the ratios of NPL, LDR, GCG, ROA, ROE, NIM, and CAR as financial performance indicators. The research method used in this study is descriptive comparative with a quantitative approach. The data used are secondary data obtained from Bank Bukopin's annual financial statements for the period 2017-2022. The sampling technique used is purposive sampling. This study uses RGEC method analysis, normality test, and hypothesis test. Based on the results of the study, the financial performance of PT Bank KB Bukopin Tbk. before the acquisition was better, with a decrease in NPL ratio and an increase in net profit. However, after the acquisition, the NPL ratio increased significantly, and net profit experienced losses. There is a significant difference with the ROA and BOPO ratios before and after the acquisition.